Edutainment, gender and intra-household decision-making in agriculture: A field experiment in Kenya - Aju, Stellamaris; Kramer, Berber; Waithaka, Lilian (International Food Policy Research Institute, 2022)
Oftentimes, a man’s opinion is valued over a woman’s, with women expected to take a back seat when decisions are made in their households and in society (Kawarazuka et al., 2019). Such social norms create unequal participation between female and male smallholder farmers in African agriculture. Additionally, it puts women in positions where they can be abused (and tolerate abuse), especially by their spouses. This is a threat to women’s empowerment, increasing gender gaps in society and within families. It is therefore imperative to address societal norms that do not allow a level playing ground for both sexes in agriculture.